PENGARUH SENAM KAKI TERHADAP PENURUNAN NEUROPATI PADA PASIEN DENGAN LUKA KAKI DIABETIK DI ASRI WOUND CARE MEDAN - Simbolon, Pomarida; Sembiring, Erika Emnina; Lase, Elisa (Jurnal Ilmiah Keperawatan, 2018)
Diabetes Mellitus is a degenerative disease with an increasing number of patients characterized by an increase in blood sugar (hyperglycemia) resulting from impaired insulin secretion, insulin performance, or both. Diabetes mellitus can result in acute and vascular metabolic disorders that can cause damage to the nervous system (neuropathy). Neuropathy is characterized by reduced loss of sensation in the leg area. Neuropathy requires pharmacologicaltreatment with the provision of drugs  and non pharmacological treatment is by exercise such as foot exercise. Foot exercise aim to smooth the blood circulation in the legs, strengthen the leg muscles, and prevent further complications.The purpose of this study was to analyze the effect of foot exercise on the reduction of neuropathy in patients with diabetic foot ulcer in Asri Wound Care Medan. Neuropathy was assessed using an observation sheet of neuropathy disabilithy score (NDS).The research used one group pre-post test design with sampling technique using purposive sampling. The population in this study were diabetic foot ulcer patients who had neuropathy in ASRI Wound Care Clinic amounting to 41 people. The number of samples in this study were 10 people. The results show the mean difference before and after intervention where the mean pre-intervention is 6.70 and post intervention 1.40. To test the effect of foot exercise on the decrease of neuropathy in patients with diabetic foot ulcer was used  Wilcoxon Sign Rank Test where obtained p value = 0.004 where p<0.05 this means that there is influence of foot exercise on decreasing neuropathy in patients with diabetic foot ulcer. The results of this study can be used as input for ASRI Wound Care Clinic, especially to nurses in order to apply foot exercises to patients with diabetes mellitus to prevent neuropathy, besides foot exercises can also be applied to patients with diabetic foot ulcer that have neuropathy to help reduce or even eliminate neuropathy.